V.S. Naipaul’s “A Turn in the South”: A Journey of the writer to unveil the spirit of South America - Neetu (Innovative Research Thoughts, 2017)
Change is the law of nature. This law is applied on all aspects of life whether it is culture, civilization or literature. Since its beginning literature has changed and developed various forms. It was during the second half of the 20th century that “an offspring of the New Journalistic novel” came into existence and was recognized as the non-fictional prose which K.R.S. Iyengar defines as: “A basket that bulges with variety: history, biography, autobiography, translation, travelogue, literary journalism.” ravelogue is one of the various forms of non-fictional prose. It is a diary and narrative of travel, sport and adventure. It is a blend of description, anecdote and personal commentary. A travelogue treats a multifarious range of things from art to science and from cookery to scientific discovery. In the words of Mallikarjun Patil:“Travelogue is a work of art like any form of literature. It is a genre of historical realistic fictional work. It is a light work but valid and interesting enough to read and enjoy it.”Honored with the prestigious Nobel Prize for literature, a Trinidadian novelist and essayist of the Indo-Trinidadian descent, Sir Vidiadhar Surajprasad Naipaul popularly known as Sir V.S. Naipaul occupies a prominent place among the most admired literary figure of the 20thcentury English Literature. Naipaul’s creative works comprise novels, short stories, travelogues and other non-fictional writings. He has travelled various parts of the world. Whatever he saw in the other parts of the world, heenjoyed and recorded it in his finest travelogues. My present paper focuses on one of the finest travelogues “A Turn in the South”which with various references to historical events, rise and growth of industries, social, cultural and religious conditionsand political upheavals presents black and white picture of South America.